Non‐Viral Gene Delivery via Membrane‐Penetrating, Mannose‐Targeting Supramolecular Self‐Assembled Nanocomplexes (Adv. Mater. 22/2013). (10th June 2013) - Yin, Lichen; Song, Ziyuan; Kim, Kyung Hoon; Zheng, Nan; Gabrielson, Nathan P.; Cheng, Jianjun
<x xml:space="preserve">Abstract</x> Supramolecular self‐assembled nanocomplexes allow mannose receptormediated endocytosis and mediate membrane transduction via the pore formation mechanism, which facilitates effective cellular internalization and endosomal escape towards highly effective gene transfection, as reported by Jianjun Cheng and co‐workers on page 3063. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>